Real exchange rates in advanced transition economies - Grubacic, Sanja; Schuster, Julian (Journal of Eastern European and Central Asian Research (JEECAR), 2015)
The recent evidence from Eastern Europe suggests that one of the major obstacles towards the adoption of euro may lie in the impact that the recession of 2008 exerted on the trajectory of real exchange rates in new member countries (European Commission, 2015). This paper aims to establish and explain the relationship between the external shocks derived from the global financial crisis and recession of 2008 and equilibrium real exchange rate in advanced transition economies of Eastern Europe. The interplay between the external and internal balances is explained by developing an inter-temporal optimizing model of the real exchange rate determination in a small open economy with structural distortions. The results of our model suggest that, in the aftermath of recession, if the Eastern European economies attempt to restore and maintain the balance between the consumption, saving, and investment, the equilibrium real exchange rate will tend to reverse its trajectory from appreciation to depreciation over time in order to encourage a greater production in the future. The equilibrium real exchange rate depreciation in the future may obtain either as a result of an increase in the direct subsidies on investment or as a result of reduced subsidies on the "net-of-investment" income. The deprecation of countries’ real exchange rate, however, may continue to act as an effective constraint against the adoption of euro. © 2015, Institute of Eastern Europe and Central Asia. All rights reserved.
Keywords: Eastern European countries; Real exchange rates; Recession; Subsidies; Transition; dept.eco